2015
DOI: 10.5539/jsd.v8n9p79
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Expanding Internally Generated Revenue in Local Government Council Areas in Nigeria

Abstract: Availability of adequate financial resources are desirous for any organization to achieve the purposes for which it is established. Local government councils in Nigeria are created statutorily to perform clearly assigned functions. Experience has however demonstrated that these councils have fallen short of achieving the objectives for which they were indorsed. Some reasons have been espoused by scholars for the failing performances of most local government councils in Nigeria. Against this backdrop, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…The study recommends that state should hands-off local government revenue, while local government management should ensure accountability and judicious utilization of revenue resources. Besides, Coker et al (2015) studied the challenges of expanding internally generated revenues in local government council areas in Nigeria. The study revealed that apart from fiscal federalism which seems hostile to local government, local governments are faced with little internal revenues to argument the federally allocated funds in order to achieves its responsibilities.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study recommends that state should hands-off local government revenue, while local government management should ensure accountability and judicious utilization of revenue resources. Besides, Coker et al (2015) studied the challenges of expanding internally generated revenues in local government council areas in Nigeria. The study revealed that apart from fiscal federalism which seems hostile to local government, local governments are faced with little internal revenues to argument the federally allocated funds in order to achieves its responsibilities.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Finance is the bedrock of any administration at both private and public sector, but most local government as an arms of public sector in developing countries faces financial problem due to low level of internally generated revenues to complement funds from the central or state government in achieving their primary objectives and constitutional or statutory responsibilities of their creation. Previous researchers, Abegunde (2019); Alao, Osakede, and Owolabi (2015); Coker, Eteng, Agishi, and Adie (2015); Dada, Adebayo, and Adeduro (2017); Eteng and Agbor (2018); Oduola, Sawaneh, Ogunbela, and Babarinde (2019) and Olusola (2011) revealed that most local government in Nigeria depends on federally allocated revenues for servicing both recurrent and capital expenditures with less focus on internally generated revenues potentials. The dwindle allocation in recent time and increase in recurrent expenditures because of the outbreak of COVID-19 pandemic has necessitated the need to re-engineered the revenue drives of the local government for future prospect and development, especially, at post pandemic era.…”
mentioning
confidence: 99%
“…The State Government is simply milking the Local Government Councils in Oyo State, leaving them with low yielding sources of internally generated revenue to develop their localities. To effectively perform its functions, develop its local area and meet all its expenditures, a Local Government Council must put in place robust machinery that would enable it generate the requisite internal revenue to augment what it receives from the federation account (Coker et al, 2015). Without adequate internally generated revenue, Local Government Councils will be unable to appreciably develop their localities, and this will make citizens lose confidence in the government as an institution.…”
Section: Internally Generated Revenue Of Local Government Councilsmentioning
confidence: 99%
“…These challenges are examined below. 1) Inability to Enact Bye-Laws One of the main problems of internal revenue generation is the inability of Local Government Councils to enact and effectively enforce bye-laws, which could enhance their revenue generation (Coker et al, 2015). This is as a result of the appointment of caretaker committees by State Government to administer Local Government Councils in Oyo State.…”
Section: Challenges Confronting Local Government Councils In Generatimentioning
confidence: 99%
“…Thus, sources of revenue for subnational governments include allocation from the central government, revenue from commercial activities of government parastatals, funding from donor agencies, tax levied on individuals, and goods and other taxable objects, to mention a few. Of these sources of revenue, rates and taxes remain viable sources of internally generated revenue (IGR) but are also among the sources that pose serious challenges in terms of collection because of the possibility of leakages created by tax evasion/avoidance or even nonremittance/diversion by collecting officials (see Coker et al 2015). Corollary to the above, the success of any government in collecting rates and taxes depends greatly on its capacity to block leakages by adopting strategic collection methods that ensure all rates and taxes are properly collected.…”
Section: The Way Forwardmentioning
confidence: 99%